2022
DOI: 10.1002/smll.202107298
|View full text |Cite
|
Sign up to set email alerts
|

Fully Printed Stretchable and Multifunctional E‐Textiles for Aesthetic Wearable Electronic Systems

Abstract: cloth materials, textiles are an ideal substrate for flexible wearable electronics due to their outstanding mechanical properties, good flexibility and softness, conformal contact with skin, and excellent wearing comfort. [11,12] Therefore, it is highly desirable to develop new smart electronic textiles (e-textiles) that can integrate the functionality of electronics and the comfort of textiles. [13,14] In particular, a facile, low-cost, and high-throughput manufacturing method for the fabrication of robust an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 49 publications
0
57
0
Order By: Relevance
“…[17][18][19] Commercially available polymeric or biobased textiles are regarded as appropriate substrates for the design and scalable manufacture of cost-effective electronic textiles due to their inherent light weight, exibility, comfort, and permeability. 20,21 However, combining novel functionality with the inherent comfort, permeability, and porous qualities of textile substrates still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Commercially available polymeric or biobased textiles are regarded as appropriate substrates for the design and scalable manufacture of cost-effective electronic textiles due to their inherent light weight, exibility, comfort, and permeability. 20,21 However, combining novel functionality with the inherent comfort, permeability, and porous qualities of textile substrates still remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…For example, when 12 V voltage is applied, the large-sized fabric heater presents a uniform temperature distribution with a saturation temperature of ∼40 °C (Figure 7g), which can be used for joint and abdominal thermotherapy. 64 In addition, we also tested the durability of the fabric heater by washing. As shown in Figure S23, after 5 washing−drying cycles, the laminated coil still maintains excellent electric heating performance, indicating good durability and wearability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figure e shows the electric heating performance of the fabric heater, and the saturation temperature increases along with the applied voltage. For example, when 12 V voltage is applied, the large-sized fabric heater presents a uniform temperature distribution with a saturation temperature of ∼40 °C (Figure g), which can be used for joint and abdominal thermotherapy . In addition, we also tested the durability of the fabric heater by washing.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In a different study, contradictory washing behavior was observed for a pressure sensor made of a non-woven fabric coated with carbon nanotubes using the nano-soldering method, which showed better water washing performance than detergent washing for a period of 48 h (Figure 10g) [266]. However, in another study, screen-printed electronic textiles with Ag ink showed a more stable electrical behavior for prolonged immersion (24 h) in water compared to immersion with synthetic perspiration for the same period (Figure 10h) [267]. The water used to wash has a certain influence on the washing efficiency and damages the functionality of the substrate, especially when there is hardness or impurities present, so the quality of the water cannot be compromised during washing.…”
Section: Washing Stressesmentioning
confidence: 95%